Efficacy and Patient Satisfaction of the Weekly DPP-4 Inhibitors Trelagliptin and Omarigliptin in 80 Japanese Patients with Type 2 Diabetes - Tosaki, Takahiro (Intern Med, 2017)
OBJECTIVE: We investigated the efficacy, safety, and patient satisfaction of once-weekly DPP-4 inhibitors (DPP-4Is). METHODS: Either of two once-weekly DPP-4Is, trelagliptin or omarigliptin, was administered alone or in combination with other antidiabetic drugs in 80 outpatients with type 2 diabetes mellitus for 3 months. The HbA1c, glycoalbumin (GA), body weight, and the Diabetes Treatment Satisfaction Questionnaire (DTSQ) scores were evaluated. RESULTS: Patients switching from other daily DPP-4Is (n=29) showed no significant changes in the HbA1c or GA levels. However, the HbA1c and GA levels of patients who had been naïve to DPP-4Is (n=37) significantly improved from 9.31±2.53% to 7.02±1.20% (p<0.001) and 26.7±11.8% to 17.3±5.7% (p<0.001), respectively. Several non-serious adverse events were reported, including nausea (n=1), abdominal distension (n=1), and constipation (n=1). In the DTSQs, the total score for six questions on the primary factors representing patient treatment satisfaction was not markedly changed in patients switching from daily to weekly DPP-4Is but was significantly improved from 21.0 to 28.0 (p<0.001) in patients naïve to DPP-4Is. CONCLUSION: These findings suggest that the use of a once-weekly DPP-4I is effective and well-tolerated in diabetes treatment and improves treatment satisfaction.